Structure prediction of a thermostable SR74 α-Amylase from Geobacillus stearothermophilus expressed in CTG-clade yeast Meyerozyma guilliermondii strain SO - Lim, Si Jie; Muhd Noor, Noor Dina; Salleh, Abu Bakar; Oslan, Siti Nurbaya (MDPI AG, 2020)
α-amylase which catalyzes the hydrolysis of α-1,4-glycosidic bonds in starch have frequently been cloned into various microbial workhorses to yield a higher recombinant titer. A thermostable SR74 α-amylase from Geobacillus stearothermophilus was found to have a huge potential in detergent industries due to its thermostability properties. The gene was cloned into a CTG-clade yeast Meyerozyma guilliermondii strain SO. However, the CUG ambiguity present in the strain SO has possibly altered the amino acid residues in SR74 amylase wild type (WT) encoded by CUG the codon from the leucine to serine. From the multiple sequence alignment, six mutations were found in recombinant SR74 α-amylase (rc). Their effects on SR74 α-amylase structure and function remain unknown. Herein, we predicted the structures of the SR74 amylases (WT and rc) using the template 6ag0.1.A (PDB ID: 6ag0). We sought to decipher the possible effects of CUG ambiguity in strain SO via in silico analysis. They are structurally identical, and the metal triad (CaI–CaIII) might contribute to the thermostability while CaIV was attributed to substrate specificity. Since the pairwise root mean square deviation (RMSD) between the WT and rc SR74 α-amylase was lower than the template, we suggest that the biochemical properties of rc SR74 α-amylase were better deduced from its WT, especially its thermostability.